5-Aminolevulinic acid-mediated sonodynamic therapy induces anti-tumor effects in malignant melanoma via p53-miR-34a-Sirt1 axis. Issue 2 (August 2015) - Hu, Zheng; Fan, Haixia; Lv, Guixiang; Zhou, Qi; Yang, Bin; Zheng, Jinhua; Cao, Wenwu
Highlights: ALA-SDT is used to treat malignant melanoma for the first time. ALA-SDT induces apoptosis and inhibits proliferation in malignant melanoma. miR-34a is involved in ALA-SDT-mediated anti-tumor effects. p53, miR-34a, and SIRT1 constitute a positive feedback loop. Abstract: Backgroud: Malignant melanoma is a very refractory skin tumor due to its high metastasis, poor prognosis, and insensitivity to chemotherapy. Sonodynamic therapy has recently evolved as a potential method to treat cancers. In this study, 5-aminolevulinic acid-mediated sonodynamic therapy (ALA-SDT) was used to treat malignant melanoma in vivo . Objective: To investigate whether ALA-SDT induces anti-tumor effects in malignant melanoma and to see if miRNAs are involved in this process. Methods: Tumor transplantation experiments in BALB/c nude mice were used to assess anti-tumor effects after ALA-SDT treatment. Cell apoptosis was evaluated by TUNEL assays and cell proliferation was measured using immunohistochemisty with anti-PCNA antibody. Microarray analysis was performed to measure miRNAs expressions. Endogenous miR-34a and its upstream and downstream genes were assayed by real-time PCR. Western blottings were used to determine these protein expressions. Intracellular ROS levels were detected by measuring the fluorescence intensity of DCF. Results: Tumor transplantation experiments revealed that ALA-SDT could inhibit mouse melanoma cell proliferation and tumor growth. Compared with the control group, TUNEL assays revealed that apoptosis was increased and proliferation was inhibited in the SDT group. Real-time PCR analysis showed 14-fold increase of miR-34a expression in the SDT group compared to the control group. In addition, ALA-SDT significantly increased intracellular ROS levels in vitro, which were almost inhibited by the ROS scavenger NAC. Also, the mRNA, total protein, and acetylation levels of p53 were increased, whereas some downstream anti-apoptotic or pro-proliferative factors of miR-34a such as BCL2, CCND1, CDK6, and SIRT1 were decreased in the SDT group compared with the control, ALA alone, and ultrasound alone groups. When miR-34a was inhibited in vitro, the protein expressions of BCL2, CCND1, CDK6, and SIRT1 recovered. By targeting SIRT1, which inhibits p53 acetylation, miR-34a promoted the transcriptional activity of p53, and finally led to increased expression of miR-34a itself. Therefore, the p53, miR-34a, and SIRT1 constituted a positive feedback loop. Conclusion: ALA-SDT showed synergistic anti-tumor effects in malignant melanoma by constituting a positive feedback loop of p53-miR-34a-Sirt1 axis.